Participatory Principal Leadership and School Financial Governance: Optimizing BOS Funds under Bureaucratic Constraints - Dharma Toding; Aman Aman (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2026)
Effective management of School Operational Assistance (Bantuan Operasional Sekolah—BOS) funds remains a major challenge in school financial governance, particularly within decentralized education systems characterized by bureaucratic constraints. This study examines how participatory principal leadership contributes to the optimization of BOS fund management at SD Negeri Malaworsai. A qualitative single-case study design was employed. Data were collected through semi-structured interviews, participant observation, and document analysis involving the principal, BOS treasurer, teachers, and school committee members. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, while trustworthiness was ensured through triangulation and member checking. The findings reveal four interconnected dimensions of effective BOS fund management: participatory planning, transparency and accountability, supportive supervision, and adaptive leadership. Participatory planning enabled stakeholders to contribute to budget prioritization, while transparency strengthened institutional trust and accountability. Supportive supervision promoted compliance and organizational learning, whereas adaptive leadership helped the school respond to funding delays, regulatory changes, and administrative demands. The findings also indicate that stakeholder participation requires continuous negotiation and coordination to balance competing interests under limited financial resources. This study proposes the Participatory Financial Governance Model, which explains how participation, accountability, supervision, and adaptive leadership interact to enhance financial governance, institutional resilience, and educational quality. The findings contribute to educational leadership and school financial governance literature by demonstrating that effective BOS fund management depends not only on regulatory compliance but also on the principal’s ability to integrate collaborative and adaptive leadership practices.